1050MPa grade tempered martensitic high strength high hole expansion steel and its preparation method
By using specific chemical compositions and a quenching and high-temperature tempering process to form a tempered martensite structure with nano-precipitates, the problem of insufficient hole expansion performance of high-strength steel is solved, achieving a match between high strength and high hole expansion rate, which is suitable for the manufacture of complex automotive parts.
Patent Information
- Application Number
- CN202310141190.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-02-21
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2043-02-21
AI Technical Summary
Existing technologies cannot meet the requirements of high hole expansion performance while ensuring high strength, which limits the potential for lightweighting automotive parts. In particular, high-strength, high-hole-expansion steel has not yet met the needs of complex forming processes.
By employing specific chemical composition design and processing techniques, including controlling the content of elements such as carbon, silicon, manganese, titanium, and molybdenum, and through quenching and high-temperature tempering processes, a tempered martensite structure with nano-precipitates is formed, ensuring a balance between high strength and pore-expanding performance.
It achieves high-strength, high-expansion steel with yield strength ≥980MPa, tensile strength ≥1050MPa, and expansion rate ≥40%, which is suitable for forming complex automotive parts and enhances the possibility of automotive lightweighting.
Smart Images

Figure CN116065094B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of high-strength steel, and particularly relates to a 1050MPa grade tempered martensitic high-strength high-hole expansion steel and a preparation method thereof. Background Art
[0002] In recent years, with the vigorous development of the automobile industry, passenger cars have higher and higher requirements for safety and fuel economy. Under the premise of ensuring automobile safety, lightweighting has become a development trend in the automobile industry. The lightweighting of automobiles is reflected in the manufacturing materials, which means that high strength, thinness and light weight are required, which will inevitably lead to higher and higher strength grades of automobile steel, and higher requirements for mechanical properties and forming properties of materials.
[0003] Many parts of the automobile body require multiple complex forming processes, such as beams, chassis and cantilevers. Usually, steel plates with high hole expansion properties are required to ensure that there is no cracking during the forming process. However, the hole expansion performance and strength of steel plates are contradictory, and high strength is usually accompanied by lower hole expansion performance. Therefore, in order to process qualified molded parts, automobile manufacturers have to use low-strength high-hole expansion steel plates with a strength of less than 600MPa, which limits the potential for weight reduction of these parts using advanced high-strength steel. For this reason, it is urgent to develop high-strength and high-strength steels that have hole expansion properties comparable to low-strength and high-strength steels, thereby promoting the development of lightweight automobiles.
[0004] At present, domestic automobile manufacturers basically use high-strength steel with a strength of less than 600MPa, and high-strength steel with a strength level of 780MPa is still in the stage of gradually starting to be used in batches, but it also puts forward higher requirements on elongation and hole expansion rate, and high-strength steel with higher strength level (greater than 1000MPa) is still in the research and development stage. Summary of the invention
[0005] The object of the present invention is to provide a 1050MPa grade tempered martensitic high-strength high-hole expansion steel and a preparation method thereof. The yield strength of the 1050MPa grade tempered martensitic high-strength high-hole expansion steel is ≥980MPa, the tensile strength is ≥1050MPa, and the hole expansion rate is ≥40%. The 1050MPa grade tempered martensitic high-strength high-hole expansion steel plate has excellent strength and hole expansion rate matching, and can meet the requirements of complex-shaped automotive parts with very high forming performance requirements, such as automobile chassis rear axle suspension swing arms, etc.
[0006] To achieve the above object, the technical solution of the present invention is:
[0007] The 1050MPa grade tempered martensitic high-strength high-hole expansion steel of the present invention contains the following chemical components and the mass percentage of each chemical component: C 0.04%-0.1%, Si 0.3%-1.0%, Mn 1.3%-2.0%, Ti0.05%-0.1%, Mo0.1%-0.2%, Nb 0.01%-0.05%, Ca 0.005%-0.006%, Cr 0%-0.5%, P≤0.005%, S≤0.005%, N≤0.003%, the balance is Fe and other inevitable impurities, and the following conditions must be met at the same time: 0.45≤Ti / Mo≤0.55.
[0008] Preferably, the chemical composition of the 1050MPa grade tempered martensitic high-strength high-hole expansion steel is: Ti / Mo=0.5, in mass percentage.
[0009] The 1050MPa grade tempered martensitic high-strength high-hole expansion steel of the present invention has a yield strength of ≥980MPa, a tensile strength of ≥1050MPa, and a hole expansion rate of ≥40%.
[0010] The microstructure of the 1050MPa grade tempered martensitic high-strength high-hole expansion steel of the present invention is tempered martensite and nano-carbides precipitated in the tempered martensite matrix.
[0011] In the composition design of the high-strength high-hole expansion steel of the present invention:
[0012] Carbon: Carbon is an important element to ensure the strength of the material, and is also one of the important elements in the present invention. As an interstitial atom in steel, it plays a very important role in improving the strength of steel, and has a great influence on the yield strength and tensile strength. Since the structure to be obtained is single-phase tempered martensite, in order to obtain high-strength steel with a tensile strength of 1050MPa, the carbon content must be ensured to be above 0.04%, and high-strength high-expansion steel with a tensile strength ≥ 1050MPa is obtained by tempering; but excessive carbon will reduce the formability and weldability of the material, and the carbon content should be controlled below 0.1%. Therefore, the carbon content should be controlled between 0.04% and 0.1%, and the preferred content is 0.06% to 0.08%.
[0013] Silicon: Silicon is a basic element in steel and is also one of the important elements in the present invention. Silicon can be effectively dissolved in the ferrite matrix to improve the strength and hardness of the material. Silicon can also expand the α zone, which is mainly because silicon increases the carbon activity and promotes the segregation of carbon to austenite, thereby promoting the formation of a two-phase structure. However, excessive silicon content affects the surface quality of hot-rolled high-hole expansion steel. Therefore, it is usually controlled at 0.3% to 1.0% in hot-rolled high-hole expansion steel, and the preferred content is 0.5%.
[0014] Manganese: Manganese is the most basic element in steel and one of the most important elements in the present invention. Manganese refines the ferrite grains by lowering the temperature at which austenite begins to transform into ferrite during cooling, so that austenite transforms into ferrite at a lower temperature. When the manganese content is too low, pearlite transformation will occur, which is not conducive to the improvement of forming performance; if the manganese content is too high, MnS inclusions will be formed, which will have a great impact on the hole expansion performance. The manganese content is generally above 1.3%; at the same time, the manganese content should not exceed 2.0%, otherwise segregation is likely to occur during the smelting process and hot cracking is likely to occur during casting. Therefore, the manganese content in steel is generally controlled between 1.3% and 2.0%, and the preferred content is 1.7% to 1.9%.
[0015] Titanium: Titanium is one of the key elements in the present invention. As a strong carbonitride-forming element, titanium has a strong bonding force with carbon and nitrogen atoms in steel, and can form carbonitrides during the rolling process. The design idea of the present invention is to obtain a large number of fine and dispersed nanocarbides by controlling the heat treatment process. Since the bonding force between nitrogen and titanium is greater than that between carbon and titanium, the nitrogen content should be controlled at an extremely low level when designing the composition. The titanium content is generally controlled between 0.05% and 0.1%, and the preferred content is 0.09%.
[0016] Molybdenum: Molybdenum is one of the key elements in the present invention. Molybdenum will delay the phase transformation of ferrite and pearlite, expand the process window, and facilitate the adjustment of the process in actual production; at the same time, the molybdenum element has the effect of improving the strength of the plate, which has a favorable effect on obtaining high-strength and high-expansion hole steel. The molybdenum element not only has a small diffusion coefficient, but also can reduce the diffusion coefficient of other composite precipitation products in the plate, thereby effectively inhibiting the coarsening of the precipitated phase at high temperature. The design idea of the present invention is to obtain a large amount of dispersed nanocarbides through high-temperature tempering treatment of the martensitic structure. Molybdenum can ensure that the nanocarbides will not coarsen during the high-temperature tempering process, thereby having a strong strengthening effect. The content of molybdenum is generally controlled between 0.1% and 0.2%, and the preferred content is 0.18%.
[0017] The composite addition of alloying elements can improve the strength of the sheet, but the more the addition, the better. Attention should be paid to the synergistic effect between the elements. As mentioned above, the key elements titanium and molybdenum in the present invention should satisfy a certain relationship to obtain high-strength and high-expansion steel. After a large number of experimental verifications, titanium and molybdenum must satisfy a certain relationship, that is, 0.45≤Ti / Mo≤0.55, so that the (Ti, Mo) C formed during high-temperature tempering can simultaneously achieve the maximum volume fraction and the minimum average size, maximize the precipitation strengthening effect, and make the strength of the sheet reach a high strength of 1050MPa.
[0018] Niobium: Niobium is one of the important elements in the present invention. Niobium in austenite mainly exists in three states: undissolved particles pin austenite grain boundaries and refine austenite grains; particles induced by deformation hinder recrystallization; dissolved niobium hinders the recovery and recrystallization of austenite and delays the ferrite phase transformation. Niobium exists in two states in ferrite: forming fine dispersed precipitates, pinning ferrite grain boundaries, playing a role in precipitation strengthening and grain refinement; existing in the matrix in a solid solution state. However, the amount of niobium added should not be too high. While forming carbides, carbon atoms will be consumed, reducing the precipitation effect of (Ti,Mo)C. Therefore, the niobium content in steel is generally controlled between 0.01% and 0.05%. The preferred content is 0.02% to 0.03%
[0019] Calcium: Calcium is one of the important elements in the present invention. The affinity of calcium to sulfur is greater than that of manganese. Adding a trace amount of calcium will convert the sulfide from MnS to CaS, which is beneficial to improving the hole expansion performance of the plate. However, excessive calcium will increase the content of CaO, which is not conducive to the hole expansion performance. Therefore, the calcium content in steel is generally controlled between 0.005% and 0.006%.
[0020] Chromium: Chromium is an element that can be added in the present invention. Chromium improves hardenability. It makes the steel have better comprehensive mechanical properties after quenching and tempering. Chromium-containing carbides can also be formed in carburized steel, thereby improving the wear resistance of the material surface. At the same time, adding chromium elements also helps to improve the tensile strength of the plate. The chromium content in the steel is controlled between 0% and 0.5%.
[0021] Phosphorus: Phosphorus is an impurity element in steel. It is very easy to segregate at the grain boundary. When the phosphorus content is high (≥0.1%), the Fe2P formed near the grain will reduce the plasticity and toughness of the plate. Therefore, the phosphorus content in steel is generally controlled within 0.005%.
[0022] Sulfur: Sulfur is an impurity element in steel. Sulfur will combine with manganese to form MnS inclusions, which seriously affects the hole expansion performance of the plate. Therefore, the lower the sulfur content, the better. Considering that the manganese content in the present invention is at a relatively high level, in order to reduce the generation of MnS, strict requirements are imposed on the sulfur content, and an appropriate amount of calcium is added to combine with sulfur. Therefore, the sulfur content in steel is generally controlled within 0.005%.
[0023] Nitrogen: Nitrogen is an impurity element in steel. Nitrogen is an inevitable element in the smelting process. Although the content is low, it has a strong ability to combine with strong carbonitride-forming elements. For example, the titanium nitride particles formed by combining with titanium will have a greater adverse effect on the hole expansion performance of the plate. Therefore, the nitrogen content in steel is generally controlled within 0.003%.
[0024] The method for manufacturing the 1050MPa grade tempered martensitic high-strength high-hole expansion steel of the present invention comprises the following steps:
[0025] S1: Smelting and casting
[0026] The raw materials are weighed according to the following composition, and smelted, refined, and continuously cast into billets or ingots, and the chemical composition mass percentage is: C 0.04%-0.1%, Si 0.3%-1.0%, Mn 1.3%-2.0%, Ti 0.05%-0.1%, Mo 0.1%-0.2%, Nb0.01%-0.05%, Ca 0.005%-0.006%, Cr 0%-0.5%, P≤0.005%, S≤0.005%, N≤0.003%, the balance is Fe and other unavoidable impurities, and the following conditions must be met at the same time: 0.45≤Ti / Mo≤0.55;
[0027] S2: Homogenization of billets or ingots
[0028] The casting blank or ingot is subjected to homogenization treatment, wherein the heating temperature is ≥1250°C and the holding time is 1 to 2 hours to obtain a homogenized casting blank or ingot;
[0029] S3: Hot rolling
[0030] The homogenized billet or ingot is hot rolled, the starting rolling temperature is 1050-1150℃, three rough rollings are performed at above 1050℃ and the cumulative deformation is ≥80%; the intermediate billet is heated to 950-1050℃, and then two large reduction finishing rollings are performed and the cumulative deformation is ≥90%; the final rolling temperature is 860-900℃;
[0031] S4: Quenching + tempering heat treatment
[0032] After the final rolling, the steel plate is water-cooled to room temperature at a cooling rate of ≥100°C / s to obtain a martensitic matrix steel plate; and then a tempering heat treatment is performed to obtain a 1050MPa grade tempered martensitic high-strength high-hole expansion steel with a nano-precipitate phase.
[0033] The tempering temperature is 600-650° C., the tempering time is 1-4 hours, and the tempering treatment is followed by air cooling to room temperature.
[0034] Compared with the prior art, the present invention has the following beneficial effects:
[0035] The composition design of the present invention adopts a lower carbon content to ensure that the plate has excellent weldability; a higher silicon content helps to improve the solid solution strengthening effect, and at the same time, more residual austenite can be obtained to improve the plasticity of the plate; Ti and Mo are precipitation phase forming elements, and a large number of nano-scale precipitation particles can be precipitated in the matrix by controlling the rolling process, which is of great benefit to the improvement of precipitation strengthening effect. The present invention sets the Ti addition amount to 0.05% to 0.1%, controls 0.45≤Ti / Mo≤0.55, and therefore, the Mo addition amount is set to 0.1% to 0.2%; adding a trace amount of Nb is mainly to refine the austenite grains in the finishing stage, and ultimately plays a role in refining the organization and improving the fine grain strengthening effect.
[0036] In terms of organizational design, the present invention adopts the design concept of quenching plus high-temperature tempering to obtain a tempered martensitic structure with nano-precipitation phase. A higher silicon content is added to inhibit cementite formation and reduce the non-recrystallization temperature. Hot rolling and rapid quenching after rolling are performed within a relatively wide final rolling temperature range, so that original austenite grains with fine and uniform grains can be obtained, which is conducive to obtaining a uniform low-carbon martensitic structure. Since tempering treatment will reduce the strength of martensitic steel, in order to compensate for the strength reduction caused by tempering and improve the hole expansion performance of the plate, the present invention appropriately increases the addition of Ti and Mo, and obtains a large number of fine and dispersed nano-carbides during high-temperature tempering. In addition, the Mo element has good thermal stability, and the (Ti, Mo) C produced by high-temperature tempering will not be significantly coarsened, thereby enhancing the precipitation strengthening effect.
[0037] In the rolling process design, the rhythm of the hot rolling process should be completed as quickly as possible. After the final rolling is completed, the plate is directly quenched to room temperature, and the dislocations in the structure increase, which helps to improve the strength of the plate; in addition, dislocations can promote carbide nucleation in the following ways: First, nucleation on dislocations can relax part of the distortion energy of dislocations, reducing the nucleation work; secondly, the solute atom gas clusters near the dislocations and the dislocations as fast diffusion channels provide favorable conditions for the formation of solute-rich cores. Therefore, after the martensitic matrix steel obtained by quenching is tempered at high temperature, a large number of fine dispersed precipitates will be formed near the dislocations. In addition, in order to obtain a martensitic structure, the water cooling rate should be greater than the critical cooling rate of low-carbon martensite. In the present invention, in order to ensure that all component designs can obtain martensite, the water cooling rate of the strip is required to be ≥100℃ / s.
[0038] In order to obtain a single-phase uniform tempered martensitic structure and nano-precipitation, it is necessary to cool the strip to the martensitic phase transformation temperature range for complete martensitic phase transformation, and then perform high-temperature tempering treatment. In the present invention, the high-temperature tempering temperature is 650°C. When the tempering temperature is lower than this temperature, the precipitation is not sufficient, the strength increase brought by the nano-carbides is less than the strength decrease caused by tempering, the overall strength decreases, and the strength requirements of more than 1050MPa cannot be met. For the above reasons, the tempering temperature needs to be controlled at 650°C. It is based on this innovative composition and process design idea that the present invention can obtain 1050MPa grade tempered martensitic high-strength high-expansion steel with excellent strength, plasticity and hole expansion performance.
[0039] The beneficial effects of the present invention are:
[0040] The manufacturing method of the present invention is used to manufacture 1050MPa grade tempered martensitic high-strength high-hole expansion steel with a yield strength of ≥980MPa, a tensile strength of ≥1050MPa, and a hole expansion rate of ≥40%, and has good strength (tensile strength ≥1050MPa) and hole expansion performance (hole expansion rate ≥40%), showing excellent strength and hole expansion performance matching, thereby bringing the following beneficial effects:
[0041] (1) By adopting a relatively economical composition design concept and an innovative quenching and tempering process path, a tempered martensite precipitation-strengthened high-strength and high-hole expansion steel with excellent strength, plasticity and hole expansion performance can be obtained;
[0042] (2) The plate has excellent strength, plasticity and hole expansion and flanging performance matching, and can be used in the manufacture of parts such as automobile chassis and subframes that require high-strength thinning and hole expansion and flanging, and has a very broad application prospect. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] Figure 1 It is a schematic diagram of the homogenization treatment and hot rolling process in the method for manufacturing the 1050MPa grade tempered martensitic high-strength high-hole expansion steel of the present invention;
[0044] Figure 2 This is a schematic diagram of the tempering process in the method for manufacturing 1050MPa grade tempered martensitic high-strength high-hole expansion steel according to the present invention. DETAILED DESCRIPTION
[0045] The present invention is further described in detail below in conjunction with embodiments.
[0046] Reference Figure 1-2 The method for manufacturing the 1050MPa grade tempered martensitic high-strength high-hole expansion steel of the present invention comprises the following steps:
[0047] 1) Smelting and casting
[0048] Smelting, refining and continuous casting into billets or ingots according to the following chemical composition, the mass percentage of which is: C 0.04%-0.1%, Si 0.3%-1.0%, Mn 1.3%-2.0%, Ti 0.05%-0.1%, Mo 0.1%-0.2%, Nb 0.01%-0.05%, Ca 0.005%-0.006%, Cr 0%-0.5%, P≤0.005%, S≤0.005%, N≤0.003%, the rest is Fe and other unavoidable impurities, and the following chemical composition mass percentages must be met at the same time: 0.45≤Ti / Mo≤0.55;
[0049] 2) Homogenization of billets or ingots
[0050] The casting blank or ingot is subjected to homogenization treatment, wherein the heating temperature is ≥1250°C and the holding time is 1 to 2 hours to obtain a homogenized casting blank or ingot;
[0051] 3) Hot rolling
[0052] The homogenized billet or ingot is rolled, the starting rolling temperature is 1050-1150℃, and the steel plate is rolled for 3 passes at a temperature above 1050℃ with a cumulative deformation of ≥80%. The intermediate billet is then heated to 950-1050℃, and then the last 2 passes are rolled with a cumulative deformation of ≥90%; the final rolling temperature is 860-900℃, and after the final rolling, the steel plate is water-cooled to room temperature at a cooling rate of ≥100℃ / s. The process diagram is shown in Figure 1 ;
[0053] 4) Tempering
[0054] The tempering temperature is 650℃, the tempering time is 1 to 4 hours, and the tempering treatment is completed and then air-cooled to room temperature. The process diagram is shown in Figure 2 .
[0055] The composition of the 1050MPa grade tempered martensitic high-strength and high-hole expansion steel embodiment of the present invention is shown in Table 1. Table 2 is the production process parameters of the 1050MPa grade tempered martensitic high-strength and high-hole expansion steel in the embodiment of the present invention, wherein the thickness of the steel billet is 34mm. Table 3 is the mechanical properties of the 1050MPa grade tempered martensitic high-strength and high-hole expansion steel plate in the embodiment of the present invention.
[0056] It can be seen from Table 3 that the yield strength of the 1050MPa grade tempered martensitic high-strength high-hole expansion steel of the present invention is ≥980MPa, the tensile strength is ≥1050MPa, and the hole expansion rate is ≥40%.
[0057] Table 1 Chemical composition of 1050MPa grade tempered martensitic high strength high hole expansion steel
[0058]
[0059] Table 2 Manufacturing process parameters of 1050MPa grade tempered martensitic high strength high hole expansion steel
[0060]
[0061]
[0062] Table 3 Mechanical properties of 1050MPa grade tempered martensitic high strength high hole expansion steel
[0063]
[0064] It can be seen from the above-mentioned embodiments that the 1050MPa grade tempered martensitic high-strength high-hole expansion steel involved in the present invention has good strength, plasticity and hole expansion performance matching, and is particularly suitable for parts such as automobile chassis structures that require high-strength thinning and hole expansion and flanging forming, such as control arms, etc. It can also be used for parts such as wheels that require flanging, and has broad application prospects.
[0065] Comparative Example 1
[0066] The same as Example 1, except that: Ti / Mo is 0.25 or 1, that is, Ti is 0.05%, Mo is 0.2% or Ti is 0.1%, Mo is 0.1%, then the yield strength and tensile strength of the experimental steel are lower than 1050MPa grade tempered martensitic high-strength steel, indicating that controlling the Ti / Mo ratio can regulate the precipitation of nano-scale (Ti, Mo)C composite particles, thereby playing an important role in improving the strength of the material.
[0067] Comparative Example 2
[0068] The same as Example 1, except that: when the mass percentage of C is 0.5%, the obtained steel has poor welding performance.
[0069] Comparative Example 3
[0070] The same as Example 1, except that: the mass percentage of Si is 0.1%, and the yield strength and tensile strength of the obtained experimental steel are both lower than those of 1050MPa grade tempered martensitic high-strength steel, indicating that a higher silicon content can provide a significant solid solution strengthening effect, which is beneficial to improving the strength of the steel.
[0071] Comparative Example 4
[0072] The same as Example 1, except that: after fine rolling and natural cooling to room temperature, the obtained steel has a yield strength of 630-750 MPa, a tensile strength of 780-850 MPa, and a hole expansion rate of 43-65%, indicating that if the cooling rate is too low, the martensitic structure cannot be obtained, thereby reducing the strength.
[0073] Comparative Example 5
[0074] The same as Example 1, except that: when the tempering temperature is 600°C, the yield strength of the obtained steel is 820-900MPa, the tensile strength is 930-970MPa, and the hole expansion rate is 35-42%, indicating that the volume fraction of nano-carbides precipitated by low-temperature tempering is reduced, the strength is reduced, and the hole expansion performance is poor. After high-temperature tempering at 650°C, the structure is transformed from martensite recovery recrystallization to equiaxed ferrite. Ferrite, as a soft phase structure, will produce large plastic deformation under the action of the stress field, and the stress concentration is relieved, which has a certain hindering effect on the expansion of cracks, so that the forming performance of the experimental steel after tempering is improved.
Claims
1. A 1050MPa grade tempered martensitic high strength high hole expansion steel, characterized in that: The chemical composition and mass percentage of each chemical component contained in the 1050MPa grade tempered martensitic high-strength high-hole expansion steel are as follows: C 0.04%-0.1%, Si 0.3%-1.0%, Mn 1.3%-2.0%, Ti 0.09%-0.1%, Mo 0.1%-0.2%, Nb 0.01%-0.05%, Ca 0.0056%-0.006%, Cr 0%-0.5%, P≤0.005%, S≤0.005%, N≤0.003%, the balance is Fe and other unavoidable impurities, and must also meet the following conditions: 0.097 / 0.19≤Ti / Mo≤0.55; The yield strength of the 1050MPa grade tempered martensitic high-strength high-hole expansion steel is ≥1006MPa, and the hole expansion rate is ≥40%; The manufacturing method of the 1050MPa grade tempered martensitic high-strength high-hole expansion steel comprises the following steps: S1: Smelting and casting The raw materials are weighed according to the following composition, and smelted, refined, and continuously cast into billets or ingots. The chemical composition mass percentage is: C 0.04%-0.1%, Si 0.3%-1.0%, Mn 1.3%-2.0%, Ti 0.09%-0.1%, Mo 0.1%-0.2%, Nb 0.01%-0.05%, Ca 0.0056%-0.006%, Cr 0%-0.5%, P≤0.005%, S≤0.005%, N≤0.003%, the balance is Fe and other unavoidable impurities, and the following conditions must be met at the same time: 0.097 / 0.19≤Ti / Mo≤0.55; S2: Homogenization of billets or ingots The casting blank or ingot is homogenized to obtain a homogenized casting blank or ingot; S3: Hot rolling The homogenized billet or ingot is rolled, the starting rolling temperature is 1120-1150°C, three rough rollings are performed at above 1120°C and the cumulative deformation is ≥80%, then the intermediate billet is heated to 950-1120°C, and two large reduction finishing rollings are performed and the cumulative deformation is ≥90%; the final rolling temperature is 860-900°C; S4: Quenching + tempering heat treatment After the final rolling, the steel plate is water-cooled to room temperature at a cooling rate of ≥100°C / s to obtain a martensitic matrix steel plate; and then subjected to tempering heat treatment to obtain a 1050MPa grade tempered martensitic high-strength high-hole expansion steel with nano-precipitated phase; In S2, the heating temperature of the homogenization treatment is ≥ 1250°C; In S4, the tempering temperature is 600-650° C., and the tempering time is 1-4 hours.
2. The 1050MPa grade tempered martensitic high strength high hole expansion steel according to claim 1, characterized in that: The tensile strength of the 1050MPa grade tempered martensitic high-strength high-hole expansion steel is ≥1050MPa.
3. The 1050MPa grade tempered martensitic high strength high hole expansion steel according to claim 1, characterized in that: The microstructure of the 1050MPa grade tempered martensitic high-strength high-hole expansion steel is tempered martensite and nano-carbides precipitated in the tempered martensite matrix.
4. The 1050MPa grade tempered martensitic high strength high hole expansion steel according to claim 1, characterized in that: In S2, the heat preservation time of the homogenization treatment is 1 to 2 hours.
5. The method for manufacturing 1050MPa grade tempered martensitic high strength high hole expansion steel according to claim 1, characterized in that: In the above S4, after the tempering treatment is completed, the mixture is air-cooled to room temperature.
Citation Information
Patent Citations
1180MPa-grade low-temperature tempered martensite high-hole-expansion steel and manufacturing method thereof
CN114107795A